Implementation of Three Metafunctions in Verbal Language and Visual Image of Students’ Textbook - Pertama, Tia; Rukmini, Dwi; Bharati, Dwi Anggani Linggar (Universitas Negeri Semarang, 2018)
This study is aimed to explain the implementation of three metafunctions in verbal language and visual image of students’ textbook to see how the meaning is processed through different modes and how they relate each other to shape a meaningful text. The subject of the study is the students as the users of the book and regarding the object of the research, this study investigated chosen data which contain verbal language and image in the students’ textbook. There are 80 pictures being analyzed in this study. This research is a descriptive qualitative and uses two instruments to collect the data. The first is the checklist of verbal analysis by Eggins (2004) to analyze the verbal language that represents three metafunctions in the textbooks. The second is the checklist table for visual image analysis by applying the theory of Van Leeuween (2006). The results of the study showed that in verbal language, the ideational metafunction is dominated by the relational process which means that the text is about giving information or attribute to something and it is realized through the nominal group of sentences. Interpersonal metafunction is dominated by statement speech acts which shows that the text mostly in the form of declarative mood. Textual metafunction contains multiple themes in this textbook to give the variety of ideas. In the visual image, ideational metafunction is realized through mostly the narrative process which is the reactional process. Interpersonal metafunction is realized through the indirect gaze with the long shot and horizontal frontal angle. The textual metafunction is dominated by the left-right value.